IBN TAIMIYAH: PENGARUH FAHAMANNYA DALAM TRADISI PEMIKIRAN ISLAM - Ahmad Nabil Amir (Universitas Hamzanwadi, 2021)
This paper analyzes the ideas and doctrines of Ibn Taimiyah (661-728/1263-1328), an acclaimed Muslim jurist, theologian and reformist in medieval Islam. His juristic opinion and influential kalam and classical school had substantial impact on contemporary Islamic religious outlook, as well as his ideology that deeply impacted the modern salafis movement. This study was conducted based on descriptive and analytical method, deriving its material from library sources, mainly from Ibn Taymiyah’s critical and groundbreaking works as well as from primary and secondary work on him. The finding shows that his theological works had intense and profound impact on classical and contemporary writings of Islamic theology that extensively derived from his fatwa (religious verdict) that informed dynamic understanding of Islam and its religious ideal.